Spatial model in the Tuvan and Old English heroic epics - Prosyannikova, Olga I.; Skorik, Kseniya V.; Grebenev, Alexander N. (The New Research of Tuva, 2023)
The article deals with spatial representations which, firstly, are basic in the human thinking consciousness and, secondly, form each ethnic group’s own model of the world. The relevance of the research is determined by the necessity of ethno-identification of cultural and historical concepts in the era of globalization. An interpenetration of cultures, which sometimes erases ethnocultural features and archetypical signs, is typical for this process. The aim of the study is to find out linguistic means of actualizing spatial relations in Tuvan and Old English epics.The study is carried out through the analysis of lexemes which represent the universal category of space. Its most important components originated in the archaic worldview and are imprinted in the epics. Such characteristics of space as partition, binary oppositions and measurement parameters constitute the cultural code and are determined by factors and conditions of living environment, traditions and customs. All these are manifested in the epic works of Tuvan and Anglo-Saxon peoples and allow to form an archetypical spatial model of the studied ethnos.As a result of the study it has been found out that the spatial models of the world, reflected in the epic works of the Tuvans and Anglo-Saxons that belong to different national and cultural autonomies, have common features in the representation of the world as a trichotomous model, in orientation to the cardinal directions and coordinate axes, in the binary opposition between “native” and “alien” spaces. At the same time, we can highlight some distinctive features of the Tuvan epos with regard to spatial representations in relation to the human body and parameters of the way and space. The authors note the symbolism of color in the description of the cardinal points of the world and the indication of the sacred places in Tuvan tales. The analysis of the linguistic means of actualizing the category of space shows that each ethnic group has its own perception of space through its assimilation and reflection in the mythopoetic model of the world.The linguoculturological approach to the study of epics of peoples of different origins allows to reveal ethnoses’ ideas about the world order and their world outlooks in the archaic period of development during which the foundations of ethnic culture and ethnocultural spirit were formed.
Keywords: epos; Tuvan heroic epics; Beowulf; category of space; spatial model